Theological Formation in Latin America before the Council - Costadoat, Jorge (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
The theological formation of Latin American seminarians before and after Vatican II underwent major changes. This article focuses on such formation before the Council. A first part outlines the directions given by the Magisterium for its purpose. In addition, the article presents the wishes about the formation («vota») that the bishops sent to John XXIII. In a second part the article exposes the Christology that was taught in the seminaries and, in particular, the content and purpose of the treatise De Verbo incarnato. The article concludes that this Christology was oriented to the formation of priests who could celebrate the Eucharist as a satisfactory sacrifice to God for sins.
Keywords: De Verbo incarnato; Christology; soteriology; seminarians; priests